Response size of Digestive organs of Broiler that are fed containing Jack bean (Canavalia ensiformis) different levels of protein with protease enzyme supplementation - Mahardhika, Brahmadhita Pratama; Ridla, Muhammad; Mutia, Rita; Naja, Miftakhun (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
This research was conducted to evaluate the use of Jack bean (Canavalia ensiformis), the level of protein diet, and the supplementation of protease enzymes to the size response of the starter phase of Broiler chicken digestive organs. Birds used in this study were 48 broilers of male chickens which were distributed into 3 observation factors and 3 replications (each replication consisted of 2 samples). The observation factor is Factor 1 are ingredients (basal diet based on soybean meal and a diet containing Jack bean), the second factor is the level of protein (22% and 19.5%) and the third factor is enzyme treatment (without enzymes and the addition of proteases). The design used was a completely randomized factorial design (RALF) and analysis of variance. The results showed that the decrease in protein level (from 22% to 19.5%) significantly high (P <.0.01) increased the length of the jejunum but could be reduced to produce the same length as basal feed (PK 22%) with the addition of the protease enzyme. The use of Jack bean significantly (P <0.05) increases the length of the jejunum but is reduced by the addition of the protease enzyme to the same as the basal diet produced by soybean meal. The addition of protease enzymes significantly reduced ileum weight and total small intestine weight (P <0.05) and significantlydecreased jejunum length (P <0.01). There was no interaction between ingredient, level of protein, and protease enzymes on size response of digestibility broiler organ.